Hydrogen for future thermal engines - Tingas, Efstathios-Al (Green energy and technology., 2023)
This book explores the potential of hydrogen combustion in thermal engines and serves as a foundation for future research. Hydrogen, a well-established energy carrier, has been used in internal combustion engines for centuries, but despite progress and industry interest, hydrogen engines have yet to reach mass production. In light of recent efforts to combat climate change with clean energy and environmentally-friendly technologies, the use of hydrogen in thermal engines is gaining momentum. This book examines the unique challenges of hydrogen combustion due to its wide flammability limits, high auto-ignition temperature, and high diffusivity. It reviews current knowledge on the fundamental and practical aspects of hydrogen combustion and considers current developments and potential future advancement.